Global MPI 2020 – Charting pathways out of multidimensional poverty: Achieving the SDGs - United Nations Development Programme (UNDP); Oxford Poverty and Human Development Initiative (OPHI) (United Nations Development Programme (UNDP) and Oxford Poverty and Human Development Initiative (OPHI), 2020)
The 2020 global MPI report profiles a global study covering 5 billion people of harmonised trends in multidimensional poverty. It explores if countries, before the pandemic, were on track to halve their multidimensional poverty if observed trends continued. In the context of COVID-19, which unfolded as the report was compiled, the report offers simulations of the possible impacts of the pandemic on the global MPI. A decade away from the targets of the 2030 Agenda for Sustainable Development, the report concludes with an in-depth analysis of multidimensional poverty from the perspective of a selection of SDGs.